Yield attributes and yields of Indian mustard (Brasssica Juncea L.) varieties as influenced by different fertility levels under timely sown rainfed conditions - P Keerthi,; Vinod Goyal,; Ram Avatar, (Journal of Oilseed Brassica, 2026)
A field experiment was conducted during rabi 2021-22 to study the yield attributes and yield of Indian mustard varietiesat the research farm, College of Agriculture, CCSHAU, Hisar, Haryana. The experiment was laid out in split plot designwith three replications consisted four mustard varieties (Kranti, RGN229, RH725 and RH1424) as main plots and threefertility levels (100% RDF, 125% RDF and 150% RDF) as subplots treatments. Results revealed that among varieties RH1424 resulted in significantly higher yield attributes and yield as compared to Kranti, RGN 229 and RH 725. Amongfertility levels, 150% RDF exhibited significantly more siliquae plant-1, higher 1000 seed weight, seed yield and stoveryield followed by 125% RDF and 100% RDF.